الأفكار والممارسات المعاصرة للخوارج في ضوء السنة النبوية : دراسة تحليلية نقدية - مرزوقي، سلمان محمد عبد الله (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
The aim of the research is to define the Khwarijis as the first group to appear in Islamic history. The Prophet (peace be upon them) warned them about the Prophet, and they have ideas and beliefs that are far from the Prophet's guidance.The strife of the Kharijites began early in the time of the Prophethood, through the era of the Caliphs until today, and continues until the the Doomsday.In this research, the researcher tries to identify the Khwarijs, their origins and appearance, and their names and their main teams. The researcher used the inductive method; he collected all the prophetic narratives related to the Khwarij and the analytical method by analyzing the Hadiths and explaining them through the sayings of the scholars with some benefits and extracting their stylistic, behavioral, And the place of their departure and the rule of their fighting and the time of their interruption.The researcher concluded through his research to the great similarity between Kharij day and yesterday, such as ignorance of religion and boldness on blood and detractors from the scientists and assassinations, and the difference is the former in the lack of worship and the fight of polytheists and resort to the land of infidelity and bullying them on the Muslim countries, and others.The researcher also presents the most prominent suspicions in the doctrine and discusses them as the interpretation of some beliefs and atonement, and suspicions about the rulers that they do not implement the law and the infidels, and the evidence that the exit of some righteous old, and suspicions related to scientists that they do not do their duty of advising the rulers and they do not understand the reality Fatwa, and suspicions related to jihad as an imposition of an eye in our time and gasification suicide bombings and suspicion of the removal of idolaters from the Arabian Peninsula, and concluded the researcher with the most important findings and a set of recommendations